Life as a clock - Harder, Hayley (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2018)
This slam poem is a reflection on 150-plus years of missing and murdered Indigenous women and girls in Canada and how this has affected Indigenous and non-Indigenous children, youth, and families.